Associations between the gut microbiota, immune cells, and different subtypes of epilepsy: A Mendelian randomization study - Xu Zhang; Zhenlin Yang; Jingjing Guo; Yuanxin Wei; Jinzi Li (Epilepsia Open)
Abstract Objective The gut microbiota (GM) plays a role in epilepsy development via the microbiota–gut–brain axis. However, its relationship with various epilepsy subtypes and its mediating role through immune cells remain unclear. Thus, identifying the GM linked to specific epilepsy subtypes and investigating immune mechanisms to predict epilepsy risk, tailor treatments, and monitor outcomes are crucial. Methods We performed a two‐sample Mendelian randomization (MR) study focused on the relationships between different epilepsy subtypes associated with the GM and the mediating role of immune cells between different epilepsy subtypes and the GM. Genome‐wide association analysis summary statistics of 412 GM species (GCST90027446–GCST90027857) and 731 immune cell phenotypes (GCST90001391–GCST90002121), along with summary statistics of different subtypes of epilepsy, were used in a publicly available genome‐wide association analysis. Significantly associated single‐nucleotide polymorphism (SNP) loci were extracted as instrumental variables according to preset thresholds, with an inverse variance weighted (IVW) model being the main model. Additionally, MR‐Egger regression, weighted median, weighted, and simple models were also used for analysis. Results MR analyses revealed the relationships of the GM and immune cells with diverse epilepsy subtypes, with no statistically significant effect of different epilepsy subtypes on the GM after correction for multiple testing via the false discovery rate (FDR) approach. Notably, one bacterial species, Gordonibacter pamelaeae, with an uncorrected low p‐value (OR: 1.0136, 95% CI: 1.0048–1.0225, p = 0.0025), was positively related to childhood absence epilepsy (CAE). Among immune cells, CD4+ ACs (OR: 1.0152, 95% CI: 1.0067–1.0238, p = 0.0005) were strongly related to CAE. Additionally, mediated effect analysis revealed that seven types of GM mediate the effects of eight immune cells on epilepsy, with Bacteroides caccae mediating CD33br HLA DR+ CD14dim AC cells producing the greatest effect on generalized epilepsy. Significance The above results demonstrate the close association between specific GM and specific immune cells in epilepsy and can be used to inform the treatment of different epilepsy subtypes by modulating the GM and immune cells. Plain Language Summary This study investigated the relationships between the gut microbiota and different epilepsy subtypes and the mediating role of immune cells. These findings emphasize that there is a close association between specific gut microbiota and specific immune cells in epilepsy and that they can be used to inform the treatment of different epilepsy subtypes by modulating the gut microbiota and immune cells.